Progress in phase field research of dead lithium in lithium batteries - Jing LIU; Huiyi CHEN; Huiyu LIU; Shu LI (工程科学学报)
In recent years, the increase in people’s demand for energy has led to the development of secondary batteries. Because of its high theoretical capacity and low electrochemical potential, lithium metal has gradually become the preferred negative electrode material for high-energy-density secondary batteries and has great application prospects in the field of energy storage technology. However, the practical application of lithium metal anodes faces major challenges mainly because of the inevitable formation of lithium dendrites and dead lithium during the charge–discharge cycle. These problems considerably reduce the Coulomb efficiency and service life of lithium metal batteries and constitute a substantial obstacle to the development and wide application of lithium metal batteries. Lithium dendrites are tree-like structures formed by uneven lithium deposition during the charging of lithium metal. These dendrites can penetrate the diaphragm and reach the cathode, causing a short circuit that can lead to catastrophic battery failure. Dead lithium refers to lithium that is separated from the anode during the discharging of a lithium battery and no longer participates in subsequent electrochemical reactions. The accumulation of dead lithium reduces the inventory of active lithium, causing battery capacity and efficiency to decline over time. Addressing these challenges requires an in-depth understanding of the formation mechanisms of lithium dendrites and dead lithium and their influencing factors. This study focuses on analyzing these mechanisms and influencing factors from the perspective of the phase field, which is a powerful computational method to simulate microstructure evolution, providing insights into the complex dynamics of lithium deposition and the conditions and influencing factors for the formation of lithium dendrites and dead Lithium. The latest research progress on the inhibition of dead lithium by temperature, pressure, diaphragm, bubble, and high active electrolyte was reviewed. First, the influence of temperature and pressure on the formation of dead lithium and the effect of two coupling fields on dead lithium are discussed. Second, starting from the diaphragm and electrolyte, the results of researchers in recent years are reviewed. For example, selecting a diaphragm with the appropriate pore size can promote the uniform deposition of lithium, better prevent the penetration of dendrites, and promote the resurrection of dead lithium. The highly active electrolyte can enhance the smooth deposition of lithium and inhibit the formation of dead lithium. These factors can regulate the deposition form of lithium to a certain extent and slow down or avoid the formation of lithium dendrites and dead lithium. By optimizing these factors, researchers can better control the deposition morphology of lithium, alleviating or even avoiding the formation of lithium dendrites and dead lithium. The phase field method is used to determine how the formation of dead lithium affects the overall life of the battery. The phase field is also used to simulate the long-term behavior of lithium metal anodes to predict the battery life under various operating conditions. Finally, this paper discusses and summarizes the shortcomings of the existing phase field method in the study of the radical elimination of dead lithium and the prospects for future development.